The Values Of Tawhid In The Peusijuek Tradition In Acehnese Society (A Study In Gintong Village, Grong-Grong Subdistrict, Pidie Regency, Aceh Province) - Nabila, Nazwa; Riza, Faisal (UNIVERSITAS PAKUAN, 2020)
Islam has monotheistic values that are able to integrate and adapt in various civilizations and cultures. Islam is accepted by various nations and civilizations. Peusijuek, a ritual believed by the people of Aceh, is connected to religious beliefs because it contains monotheistic values that must be carried out. The Peusijuek tradition is part of Acehnese culture which has long been practiced by the Gintong Village Community, usually with the aim of safety, peace and happiness in life. As a cultural heritage, Peusijuek is rich in special values and meaning. This research aims to reveal how Peusijuek is believed and interpreted as a belief by the community. Even though it is religious, this does not entirely come from religious teachings. This research uses a qualitative method with a descriptive approach. The results of the research show that the Peusijuek tradition in Gintong Village contains monotheistic values which acknowledge the existence and oneness of Allah as creator, which then becomes part of the community's beliefs. The values of monotheism include monotheism uluhiyah, monotheism rububiyah, and monotheism Asma' wa sifat.